CONCENTRICALLY ZONAL TEXTURES IN A SAMPLE OF THE KAIDUN METEORITE - Ivanov A.V.; Ivanova M.A.; Kononkova N.N. (My University, 2007)
The paper reports the results of the textural and mineralogical studying of clast Kaidun #d6A. The principal minerals of the clast are phyllosilicates, carbonates, and sulfides, but the clast contains no anhydrous silicates. The clast is characterized by extremely high concentration of inclusions, which broadly vary in size, composition, and texture, from completely remelted to practically unchanged when brought to the parent body. The latter group includes two inclusions having a concentrically zonal texture, which have never before been found in meteorites. One of the inclusions consists of serpentine replaced by talc in the margins. The inclusion was formed in relation to silification under the effect of silicon-bearing aqueous fluid at a temperature of more than 300°C. The other inclusion consists of alternating Ca carbonate and phyllosilicate zones. The texture and composition of the inclusion suggest that its genesis was related to the metasomatic alteration of carbonates under the effect of silicon- and alumina-bearing aqueous fluids at temperatures of about 400–500°C. These processes are typical of large differentiated planets, and there are no reasons to expect them in the parent bodies of carbonaceous chondrites, such as Kaidun. Our results obtained on clast #d6A are in good agreement with the hypothesis that the parent body of the Kaidun meteorite was Phobos [1]. Correspondingly, inclusions #d6Aa and #d6Ab likely originated from Mars, as previously examined alkali-rich clasts did. The clast described in this publication seems to originate from the surface regolith of Phobos, which was compacted in the process of the aqueous alteration of the material and subsequently buried at a greater depth.